PMO-155 Low pre-treatment HBsAG plasma levels, on therapy HBsAG levels decline and IP-10 concentrations increase predict response to treatment in tolerant children with chronic hepatitis B. (28th May 2012) - Carey, I; Bruce, M J; Hussain, M; Horner, M; Bansal, S; Vergani, D; Mieli-Vergani, G
Abstract : Introduction: Changes in HBsAg plasma levels during antiviral therapy with pegylated interferon (IFN) predict response in chronic hepatitis B (CH-B). High baseline plasma levels of inducible interferon-γ protein 10 (IP-10) predicted HBsAg loss in CH-B adults patients on nucles(t)ide analogues (NA) therapy. No data are available on the relationship between IP-10 and HBsAg plasma levels in children with infancy-acquired CH-B on combination therapy. Aims: To investigate whether baseline plasma IP-10 levels and their changes during therapy can help to predict HBsAg loss in children with infancy-acquired CH-B on combination therapy with lamivudine (LAM) and IFN-α. Methods: Patients: 23 children (eight males, median age 10.2 yrs) with infancy-acquired CH-B (all HBeAg+), treated for 52 weeks [lead-in LAM (3 mg/kg/d) for 9 weeks; LAM plus IFN-α (5 MU/m 2 TIW) from week 9 for 44 weeks], were divided according to treatment response: five responders (R = anti-HBs seroconversion) and 18 non-responders (NR). Methods: Plasma IP-10, HBsAg and AST levels were measured in serial samples before (treatment week 0, TW0), during (TW9, TW28, TW52) and after (follow-up week, FUW24) therapy by ELISA [pg/ml], Abbott ARCHITECT® assay [log10 IU/ml] and AutoAnalyser [IU/l]. The results are presented median. Results: Baseline IP-10 levels were similar in R and NR (123 vs 99, p=0.4), but increased significantly in R than NR at TW28 (220 vs 79, p=0.04). Baseline HBsAg levels were lower in R than NR (4.36 vs 4.74, p=0.02), but similar in R and NR at TW9 (4.34 vs 4.66, p=0.1) and markedly lower in R than NR during IFN add-on therapy and therapy follow-up (TW28: 2.34 vs 4.33; TW52: 0 vs 4.08 and FUW24: 0 vs 4.51; p<0.01 for all). Baseline AST levels were similar in R and NR (29 vs 31, p=0.6) and tended to be higher in R than NR at TW28 (47 vs 32, p=0.07). At TW28, there was an inverse correlation between IP-10 and HBsAg levels (r=−0.45, p=0.03), but no correlation with AST. Conclusion: Low baseline HBsAg levels, HBsAg plasma levels decline and IP-10 concentrations increase during interferon add-on at TW28 predict HBsAg loss and response to therapy in tolerant children with CH-B. Competing interests: I Carey grant/research support from: BMS, Gilead, M Bruce: None declared, M Hussain: None declared, M Horner: None declared, S Bansal: None declared, D Vergani: None declared, G Mieli-Vergani: None declared.